Mortality And Economic Impact of African Swine Fever (ASF) Outbreak on Pigs in Luwu Timur Regency - Suartana, Dewa Putu; Suryanto; Arzam, Taruna Shafa (Global Writing Academica Researching and Publishing, 2024)
Understanding the impact of ASF comprehensively is a crucial step in efforts to control and prevent future outbreaks. Therefore, an in-depth study is needed on the